The phospholipid profile of T cells shapes ACSL4 dependency and ferroptosis sensitivity of naive, effector, and memory T cells - Gariné Magarditchian; Ivan Berest; Aikaterini Ziogou; Mai Matsushita; Michelle Reid; Alaa Othman; Manfred Kopf (Proceedings of the National Academy of Sciences, 2026)
Iron-dependent phospholipid (PL) peroxidation, which is reduced by glutathione peroxidase 4, is recognized as the hallmark of cells undergoing ferroptosis. Although studies have attempted to elucidate the molecular mechanisms underlying ferroptosis in cancer cells, the regulation of ferroptosis in effector and memory T cells remains largely unknown. Here, using genome-wide CRISPR-Cas9 knockout screens, we demonstrate that acyl-CoA synthetase long-chain family member 4 (ACSL4) is the predominant ferroptosis inducer in primary T cells cultured in vitro, while other identified iron- and lipid metabolism–related genes only slightly modulate their sensitivity to ferroptosis. However, ACSL4 dependency relies on the PL composition of the cells. In vitro cultured T cells treated with polyunsaturated fatty acids (PUFAs), as well as effector CD8 + T cells that are enriched in PUFA-containing PLs (PUFA-PLs), undergo ferroptosis in the absence of ACSL4. In contrast to effector T cells, naive and memory T cells share a similar PL profile, characterized by a scarcity of PUFA-PLs, and are resistant to ferroptosis. Overall, the PL composition is a central feature and determines the differential susceptibility of effector and memory T cells to ferroptosis and its molecular mechanism.